China's environmental policy in terms of European Union standards (Edition 1) - Tkaczyński, Jan Wiktor (2020)
It is beyond dispute that both China and the European Union stand to gain from promoting low-carbon development through the dissemination of clean and renewable energy sources, as this inevitably leads to increased environmental protection. The depletion of fossil fuel resources and the accompanying changes in the global energy mix make Europe and China not only competitors in the global economic race, but also nolens volens partners. Their pragmatic partnership is characterized, on the one hand, by the need to take action to reduce the consumption of fossil fuels and, on the other, by the desire to minimize the negative environmental impact of their use. Hence, the existing and emerging cooperation between the two actors, while challenging for a number of reasons, is not only an attempt to set up channels to exchange vital information, but also an exercise in setting the standards under which further cooperation will be forged.